The Pressure Quantity Prognosing at the Salts and Clay Disclosure on the Casing Column - Soloviev, Veniamin; Nesterenko Jr., TÐµtiana; Pedchenko, Larisa; Bida, Sergiy (International Journal of Engineering and Technology, 2018)
The stages of the fastening interaction with the breed in time are considered, based on new ideas about the interaction of rigid fastening with a dissected inelastic deformed rock whose volume is limited to the reduced pressures region and which falls to the overlap under unbalanced conditions. The method of durability determination at single-compression compression depending on the seam is developed. On the basis of research on the rock salt creep at various stresses at the stage of established creep, a dependence of the density change as a function of the velocity of creep is obtained. The experimental results of determining the salt rocks strength, depending on the velocity of their inelastic deformation, are confirmed by the practical calculations of the casing interaction with the attachment of sections of bischofite, galite and haloperitone.Â